APPLICATION OF BANANA STARCH AND BANANA FLOUR IN VARIOUS FOOD PRODUCT: A REVIEW - R Fida; G Pramafisi; Y Cahyana (Politeknik Pembangunan Pertanian Manokwari, 2019)
Banana, a botanically berry, is an edible fruit produced by several kinds of large herbaceous flowering plants in the genus Musa. Banana has been known as an abundant fruit in Indonesia. Badan Pusat Statistik shows that in 2017, the production of banana in Indonesia was the highest among other fruits (7.16 million tons in 2017), showing a 2.22% increasing rate from the last year. Banana can be directly eaten when it is ripe, or can be processed first while it is unripe. Banana, while it is unripe, contains high carbohydrate with 17.2- 38% starch in it. This starch fraction, whether it is in native state or modified state, can be extracted and can be used for many purposes in food production means such as in producing cookies, pasta etc. Many studies has been accomplished to learn the characteristics of products that are made by substituting some of the flour using banana starch. Compared to the product that are made by using 100% wheat flour, products that are made by substituting some of the flourusing banana starch have some differences in physical and chemical characteristics, digestibility, sensory properties and acceptability. This review article are meant to elaborate the uses of banana starch flour in food production and its effect to those products characteristics.